Glycopeptide Resistance among Coagulase-Negative Staphylococci that Cause Bacteremia: Epidemiological and Clinical Findings from a Case-Control Study - Tacconelli, Evelina; Tumbarello, Mario; de Gaetano Donati, Katleen; Bettio, Manola; Spanu, Teresa; Leone, Fiammetta; Sechi, Leonardo A.; Zanetti, Stefania; Fadda, Giovanni; Cauda, Roberto (Clinical infectious diseases, 2001)
A 1-year prospective case-control study (ratio of control patients to case patients, 3 : 1) was performed to assess the incidence, risk factors, and genotypic patterns of bacteremia caused by glycopeptide-resistant coagulase-negative staphylococci (CoNS) and their correlation with hospital glycopeptide use. Among 535 subjects with CoNS bacteremia, 20 subjects had a glycopeptide-resistant strain (19 strains were resistant to teicoplanin and 1 was resistant to both teicoplanin and vancomycin). The percentage of resistant isolates recovered in 1 year was 8% in intensive care units and 3% and 2% in medical and surgical wards, respectively. Genotypic analysis of resistant strains showed different patterns with a high degree of polymorphism. Use of glycopeptides in individual wards was not statistically associated with the percentage of resistance. Previous exposure to β-lactams and glycopeptides, multiple hospitalization in the previous year, and concomitant pneumonia were significantly associated with the onset of glycopeptide-resistant CoNS bacteremia. Mortality rates were 25% among case patients and 18% among control patients, and they were significantly higher among patients who presented with concomitant pneumonia and a high Acute Physiology and Chronic Health Evaluation III score.